PENGARUH PERCEIVED VALUE, BRAND IMAGE TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER ENGAGEMENT SEBAGAI VARIABEL MEDIASI (STUDI PADA PELANGAN INDIHOME PT. TELKOM MANADO) - Amir, Amriah; Mandey, Silvya L.; Tawas, Hendra N. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
The study aims to analyze the effect of Perceived Value and Brand Image on Customer Loyalty with Customer Engagement as a Mediation Variable for Indihome Customers at PT. Telkom Manado. The population of this research were Indihome customers in Manado. Sampling was carried out based on Isaac Michael's table of 267 respondents. The research data were analyzed using PLS SEM (Partial Least Square - Structural Equation Modeling) with SmartPLS 3.0 software. The results showed that Perceived Value and Brand Image had an effect on Customer Engagement but did not directly influence Customer Loyalty. Perceived Value and Brand Image affect Customer Loyalty through Customer Engagement with full mediation. Customer Engagement affects Customer Loyalty. Indihome at Telkom Manado has already good at Perceived Value and Brand Image.Â  However, the product still couldn't drive the loyal customers to buy any add-on services or ensure to a long time subscription. The company need to find strategies that can improve the customer engagement and customer loyalty with Indihome as a product.Â Keywords : Perceived Value, Brand Image, Customer Engagement, Customer Loyalty